2019
DOI: 10.1073/pnas.1819869116
|View full text |Cite
|
Sign up to set email alerts
|

MDA-7/IL-24 regulates the miRNA processing enzyme DICER through downregulation of MITF

Abstract: Melanoma differentiation-associated gene-7/interleukin-24 (mda-7/IL-24) is a multifunctional cytokine displaying broad-spectrum anticancer activity in vitro or in vivo in preclinical animal cancer models and in a phase 1/2 clinical trial in patients with advanced cancers.mda-7/IL-24targets specific miRNAs, including miR-221 and miR-320, for down-regulation in a cancer-selective manner. We demonstrate thatmda-7/IL-24, administered through a replication incompetent type 5 adenovirus (Ad.mda-7) or with His-MDA-7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Accumulating evidence has demonstrated that miRNAs are involved in cell proliferation, migration, and invasion in malignancy, such as lung cancer bone metastasis 11,13,14,17,19 . For instance, HE et al 29 revealed that downregulation of miR-20b may dramatically suppress H22 cell proliferation by directly targeting PTEN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has demonstrated that miRNAs are involved in cell proliferation, migration, and invasion in malignancy, such as lung cancer bone metastasis 11,13,14,17,19 . For instance, HE et al 29 revealed that downregulation of miR-20b may dramatically suppress H22 cell proliferation by directly targeting PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are endogenous, small, noncoding and highly conserved RNAs 11,12 . Recent studies have revealed that miRNAs are implicated in various cellular processes [13][14][15] . In addition, many studies have already demonstrated that miRNA dysfunction is involved in the occurrence and progression of malignancies, such as breast cancer, gastric carcinoma, prostate cancer, and lung cancer [16][17][18][19] .…”
mentioning
confidence: 99%
“…In 2019, one novel study showed that melanoma differentiation-associated gene-7/interleukin-24 (mda-7/IL-24), a multifunctional cytokine, displayed broad-spectrum anticancer activity by regulating the function of DICER. This study provides a new anticancer method in which key miRNA enzymes, such as DICER, are targeted to disrupt miRNA synthesis in cancer cells (28).…”
Section: Biogenesis Of Mir-27a In Solid Tumorsmentioning
confidence: 99%
“…MDA-7/IL-24 induces the expression of the chaperone protein BiP/GRP78, which in turn results in endoplasmic reticulum (ER) stress and cell death [16]. Additionally, this cytokine regulates toxic autophagy through a miR-221-Beclin-1 axis [17, 18]. MDA-7/IL-24 also has anti-angiogenic activity and it inhibits invasion and metastasis of cancer cells (1).…”
Section: Introductionmentioning
confidence: 99%